Portfolio rebalancing in general equilibrium - Kimball, Miles S.; Shapiro, Matthew D.; Shumway, Tyler; Zhang, Jing (Journal of Financial Economics, 2020)
This paper develops an overlapping generations model of optimal rebalancing where agents differ in age and risk tolerance. Equilibrium rebalancing is driven by a leverage effect that influences levered and unlevered agents in opposite directions, an aggregate risk tolerance effect that depends on the distribution of wealth, and an intertemporal hedging effect. After a negative macroeconomic shock, relatively risk-tolerant investors sell risky assets, while more risk-averse investors buy them. Owing to interactions of leverage and changing wealth, however, all agents have higher exposure to aggregate risk after a negative macroeconomic shock and lower exposure after a positive shock.